2016
DOI: 10.1002/cnma.201500228
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Dual Emission from Sucrose‐Derived Carbon Nanodots: A Ratiometric Fluorescent Thermometer

Abstract: Carbon nanodots( CNDs) with conspicuous dual emission (at 450 and5 17 nm) were fabricatedb yh ydrothermal treatment of aqueous sucrose solution.T he temperature-dependent photoluminescence (PL) and time-resolved PL werei nvestigated. The trapping of excited electrons by the nonradiative defects should substantially account for the PL quenching as the temperature increases. The sucrose-derivedC NDs show great potential for applications as ratiometric fluorescent thermometers with asensitivity of approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
(123 reference statements)
1
7
0
Order By: Relevance
“…Figure 6b). Differential temperature dependence for the low-and highenergy emission spectra of CD has also been reported by Gan et al 52 In the case of weakly emissive H-aggregate, an increase in intensity with increase in temperature is predictable, but this has to be exceedingly sufficient to overcome the strong decrease in isolated chromophore intensity due to its increase in nonradiative deactivation, even though the isolated chromophores have a small population in the blue-or redshifted excitation wavelength. However, with red-shifted excitation, assuming it to be J-aggregate, one would expect a drastic decrease in intensity with a rise in temperature compared with that with isolated chromophore or monomer emission.…”
supporting
confidence: 62%
“…Figure 6b). Differential temperature dependence for the low-and highenergy emission spectra of CD has also been reported by Gan et al 52 In the case of weakly emissive H-aggregate, an increase in intensity with increase in temperature is predictable, but this has to be exceedingly sufficient to overcome the strong decrease in isolated chromophore intensity due to its increase in nonradiative deactivation, even though the isolated chromophores have a small population in the blue-or redshifted excitation wavelength. However, with red-shifted excitation, assuming it to be J-aggregate, one would expect a drastic decrease in intensity with a rise in temperature compared with that with isolated chromophore or monomer emission.…”
supporting
confidence: 62%
“…And the measurement of PL lifetime is time‐consuming with necessity of expensive equipment like time correlated single photocounting system . Therefore, a favorable fluorescent sensor type is ratiometric . Nikitin et al's work suggested that PL of FF MTs can practically serve as a ratiometric thermometer at low temperatures .…”
Section: Applicationsmentioning
confidence: 99%
“…Thus, fluorescent technique based on pH-sensitive probes is a sensitive, convenient, and noninvasive method, which provides a powerful tool to measure the pHi of intact cells and subcellular regions. In particular, ratiometric sensors based on fluorophores with two emission peaks can avoid the interference of variations in the local probe concentration, temperature, and optical path length [ 13 , 14 , 15 , 16 , 17 , 18 ]. In recent years, great efforts have been made to develop ratiometric fluorescent pH sensors [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%